SISTEM INFORMASI PERAMALAN PERSEDIAAN OBAT MENGGUNAKAN METODE WEIGHTED MOVING AVERAGE BERBASIS WEBSITE (STUDI KASUS PT. BARRIZ SANTUN JAYA) - Kusmiatun; Tanhella Zein Vitadiar; Ahmad Heru Mujianto; Kistofer, Terdy (Fakultas Teknologi Informasi, 2024)
This study aims to build a pharmaceutical drug inventory forecasting system at PT Barriz Santun Jayausing the Weighted Moving Average method and error accuracy using Mean Absolute Percentage Error(MAPE). The object of forecasting in this study is drugs that fall into the fast moving category or drugsthat sell faster. The results of the research conducted by the system can provide comparative informationbetween actual data and forecasting results, besides that the system can display the estimated druginventory in the following month and produce an error using MAPE, while the forecasting results fall intothe category of being quite feasible in predicting the stock of fast moving drug supplies at PT BarrizSantun Jaya because it has an average error value between 20% - 23%. In conclusion, it is necessary tocompare using other methods, in order to see the accuracy of the forecasting results, while the accuracy ofthe error results can be minimized by comparing through calculations in certain periods, until you get atotal weight that is considered appropriate for forecasting.Keywords: Forecasting, Pharmaceutical Drugs, Weighted Moving Average, Website.